Psychic Numbing Al-Qur’an For Interpretation of verses of morality - Saiul Anah; Isa, Abdullah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
The Qur'an emphasizes the importance of mental health in human life and the need for peace of mind, determination, and emotional balance in facing life's challenges the behavior or attitude of